Biomarkers reveal sea turtles remained in oiled areas following the Deepwater Horizon oil spill. Issue 7 (23rd September 2016) - Vander Zanden, Hannah B.; Bolten, Alan B.; Tucker, Anton D.; Hart, Kristen M.; Lamont, Margaret M.; Fujisaki, Ikuko; Reich, Kimberly J.; Addison, David S.; Mansfield, Katherine L.; Phillips, Katrina F.; Pajuelo, Mariela; Bjorndal, Karen A.
Abstract: Assessments of large‐scale disasters, such as the Deepwater Horizon oil spill, are problematic because while measurements of post‐disturbance conditions are common, measurements of pre‐disturbance baselines are only rarely available. Without adequate observations of pre‐disaster organismal and environmental conditions, it is impossible to assess the impact of such catastrophes on animal populations and ecological communities. Here, we use long‐term biological tissue records to provide pre‐disaster data for a vulnerable marine organism. Keratin samples from the carapace of loggerhead sea turtles record the foraging history for up to 18 years, allowing us to evaluate the effect of the oil spill on sea turtle foraging patterns. Samples were collected from 76 satellite‐tracked adult loggerheads in 2011 and 2012, approximately one to two years after the spill. Of the 10 individuals that foraged in areas exposed to surface oil, none demonstrated significant changes in foraging patterns post spill. The observed long‐term fidelity to foraging sites indicates that loggerheads in the northern Gulf of Mexico likely remained in established foraging sites, regardless of the introduction of oil and chemical dispersants. More research is needed to address potential long‐term health consequences to turtles in this region. Mobile marine organisms present challenges for researchers to monitor effects of environmental disasters, both spatially and temporally. We demonstrate that biological tissues can reveal long‐term histories of animal behavior and provide critical pre‐disaster baselines following an anthropogenic disturbance or natural disaster.